Association between Tooth Loss Severity, Dietary Modifications, and Gastrointestinal Disorders in Adults: Implications for Nutritional and Functional Well-Being - Muhammad Furqan Ehsan Khan, Rashid Javaid, Jai Dev Maheshwari, Madiha Khalid Memon, Saher Sultan, Sheema Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tooth loss is a common oral health problem that affects chewing efficiency and may lead to dietary modifications and gastrointestinal (GI) disturbances. Understanding this relationship is essential for improving nutritional and functional well-being among adults. Objective: To assess the association between tooth loss severity, dietary modifications, and gastrointestinal disorders among adults attending dental and clinical facilities. Methods: A cross-sectional analytical study was conducted at Shaheed Mohtarma Benazir Bhutto Medical College and de Montmorency college of Dentistry, Lahore from May 2022 to March 2023. A total of 110 adults were enrolled. Tooth loss severity was clinically assessed and categorized as mild, moderate, severe, or edentulous. Dietary modifications were evaluated using a structured questionnaire. GI symptoms, including gastroesophageal reflux disease (GERD) and functional dyspepsia, were assessed using validated tools. Nutritional and functional status were also recorded. Data were analyzed using multivariable regression. Results: Increasing tooth loss severity was significantly associated with higher dietary modification scores (p < 0.001). Severe and edentulous participants showed marked avoidance of fibrous foods and greater dependence on soft or liquid diets. GERD prevalence increased from 18.5% in mild tooth loss to 61.1% in edentulous adults (p < 0.001). Severe tooth loss independently predicted GERD (AOR = 3.12; 95% CI: 1.32–7.35) and functional dyspepsia (AOR = 3.14; 95% CI: 1.27–7.51). Nutritional risk rose progressively with greater tooth loss, affecting 72.2% of edentulous individuals. Dietary modification partially mediated the relationship between tooth loss and GI symptoms. Conclusion: Tooth loss severity is strongly associated with dietary restrictions, increased gastrointestinal symptom burden, and a higher risk of malnutrition. Maintaining functional dentition and providing integrated dental, nutritional, and gastrointestinal care may significantly improve adult health outcomes. Keywords: Tooth loss, gastrointestinal disorders, dietary modification, GERD, dyspepsia, nutrition, adults.